Studies Calculated a New Chitin Oligomer Binding Site Inside Vicilin: A Potent Antifungal and Insecticidal Agent - Ahsan Saeed; Zahra Rafiq; Muhammad Imran; Qamar Saeed; Muhammad Q. Saeed; Zahid Ali; Rana K. Iqbal; Saber Hussain; Binish Khaliq; Sohaib Mehmood; Ahmed Akrem (SAGE Publishing, 2022)
Vicilins are major seed storage proteins and show differential binding affinities toward sugar moieties of fungal cell wall and insect gut epithelium. Hence, purpose of study is the thorough in-silico characterization of interactions between vicilin and chitin oligomer followed by fungal and insecticidal bioassays. This work covers the molecular simulation studies explaining the interactions between Pisum sativum vicilin ( Ps V) and chitin oligomer followed by protein bioassay against different pathogens. LC-MS/MS of purified Ps V (∼50 kDa) generated residual data along high pea vicilin homology (UniProtKB ID; P13918). Predicted model ( Ps V) indicated the characteristic homotrimer joined through head-to-tail association and each monomer is containing a bicupin domain. Ps V site map analysis showed a new site (Site 4) into which molecular docking confirmed the strong binding of chitin oligomer (GlcNAc) 4 . Molecular dynamics simulation data (50 ns) indicated that chitin-binding site was comprised of 8 residues (DKEDRNEN). However, aspartate and glutamate significantly contributed in the stability of ligand binding. Computational findings were further verified via significant growth inhibition of Aspergillus flavus , A. niger, and Fusarium oxysporum against Ps V. Additionally, the substantial adult population of Brevicoryne brassicae was reduced and different life stages of Tribolium castaneum also showed significant mortality.